Type IV secretion system of Brucella spp. and its effectors - Ke, Yuehua; Wang, Yufei; Li, Wengfeng; Chen, Zeliang (Frontiers in Cellular and Infection Microbiology, 2015)
Brucella spp. cause brucellosis in domestic and wild animals. They are intracellular bacterial pathogens and used as model organisms to study intracellular bacterial infections. Brucella VirB T4SS is a key virulence factor that plays important roles in mediating intracellular survival and manipulating host immune response to infection. In this review, we will discuss roles of Brucella VirB T4SS and in more detail of all 15 identified effectors, which may be crucial for Brucella pathogenesis. VirB T4SS regulates the inflammation response and manipulates vesicle trafficking inside host cells, suggesting that it plays crucial roles in the inhibition of the host immune response and intracellular survival during infection. So, we listed some key molecular events in the intracellular life cycle of Brucella potentially targeted by the VirB T4SS effectors. Elucidating functions of the effectors secreted will be crucial to clarifying mechanism of T4SS during infection. Studying the effectors secreted by Brucella spp. might provide insights into the mechanisms by which the bacteria hijack the host signaling pathways, which help us to develop better vaccines and therapies against brucellosis.